Response of Maize (Zea mays L.) Grown for Grain After the Application of Sewage Sludge - Grażyna SZYMAŃSKA; Hanna SULEWSKA; Karolina ŚMIATACZ (Journal of Central European Agriculture, 2016)
The aim of this study was to assess the effects of the agricultural use of sewage sludge in corn for grain, in the year of application and follow up effect after one and two years after its application. The study was conducted on the variety PR39G12 on the field after the 5-year monoculture corn. Sewage sludge was used in accordance with the Directive of Minister of Environment allowing application of 10 t dry mater per ha-1 once every five years. Fertilization with sludge of maize grown for grain did not cause differences in the growth and development of plants, compared to mineral fertilized objects, as well as did not exceed the limit value for heavy metals content in above-ground plant parts. Maize grown using sewage sludge yielded higher than the objects fertilized with mineral, especially in conditions of extreme drought, which occurred in 2006. Beneficial effect of sewage sludge was maintained in the next two years after application and stabilized the grain yield of maize.